Marangoni Flow-Driven Self-Assembly of Biomimetic Jellyfish-like Hydrogels for Spatially Controlled Enzyme Catalysis - Aoxiang Zhang; Huiying Zhou; Yanhui Guo; Yu Fu (Surfaces, 2025)
Enzymatic catalysis has gained significant attention in green chemistry due to its high specificity and efficiency under mild conditions. However, challenges related to enzyme immobilization and spatial control often limit its practical applications. In this work, we report a Marangoni flow-driven strategy to fabricate a biomimetic jellyfish-like hydrogel with tunable tentacle-like structures. The formation process occurs entirely in an aqueous system without organic solvents or post-treatment, enabling the construction of ultra-thin, free-standing hydrogels through spontaneous interfacial self-assembly. The resulting structure exhibits high surface-area geometry and excellent biocompatibility, providing a versatile platform for localized enzyme loading. This method offers a simple and scalable route for engineering soft materials with complex morphologies, and expands the design space for bioinspired hydrogel systems.